An Implementation: Automated Testing of Object Oriented Modules using ML UNIT Tool - Er. Krishan Kumar,; Vasu Dev, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Software testing has been considered as a process of checking correctness of software by considering its all attributes such as Reliability, Scalability, Portability, Re-usability, Usability. It is evaluating execution of software components to find software bugs or errors or defects. This research has investigated scope of manual and automation testing. The Matlab has been used as simulation tool and MLUNIT is testing tool. The functional and object oriented modules have been testing using manual and automation testing. The test suits have been developed and tested to compare actual outcome to required outcome. Validation and verification of code is required because of ever-increasing complexity of embedded software applications, and emergence of safety critical applications. Several embedded software development groups are using models and doing up front engineering before testing on final product to address this need. Use of old style of testing late in development cycle resulted in very expensive release cycles. To ensure that all of the software's features, including its reliability, scalability, portability, re-usability, and usability, are working properly, testing is performed. Testing is the process of running software in order to locate flaws. This research has investigated scope of manual and automation testing. The Matlab has been used as simulation tool and MLUNIT is testing tool. The functional and object oriented modules have been testing using manual and automation testing. The test suits have been developed and tested to compare actual outcome to required outcome. Embedded software applications are becoming more complicated, and there is a corresponding increase in the number of safety-critical applications. Some embedded SD teams are responding to this need by doing up-front engineering and modelling activities before releasing a product for testing. Inexpensive release cycles were the consequence of using antiquated testing methods late in the development cycle.
Keywords: Software testing; Automated Testing; MLUNIT